2023
DOI: 10.1177/13524585231185045
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to systemic antibiotics in outpatient care and the risk of multiple sclerosis

Abstract: Background: Infections, early life exposures and the microbiome have been associated with the aetiology of multiple sclerosis (MS). Data on any possible roles of antibiotics is scarce and conflicting. Objective: The objective of this study was to investigate associations between outpatient systemic antibiotic exposure and the risk of MS in a nationwide case-control setting. Methods: Patients with MS were identified from the nation MS registry and their exposure to antibiotics was compared with that of persons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…These results suggest that antibiotic use might not be a suitable indicator of bacterial infection to investigate the cause of MS [42]. These results were confirmed by a recent study that demonstrated no relationship between antibiotic exposure and the risk of MS [43]. Minocycline is a second-generation tetracycline that can cross the blood-brain barrier at clinically effective levels due to its lipophilic nature.…”
Section: Beta-lactam Antibioticsmentioning
confidence: 59%
“…These results suggest that antibiotic use might not be a suitable indicator of bacterial infection to investigate the cause of MS [42]. These results were confirmed by a recent study that demonstrated no relationship between antibiotic exposure and the risk of MS [43]. Minocycline is a second-generation tetracycline that can cross the blood-brain barrier at clinically effective levels due to its lipophilic nature.…”
Section: Beta-lactam Antibioticsmentioning
confidence: 59%